Happiness in the Philosophical View of Al-Ghazali And Al-Farabi - Tarwiyyah, Hanik L. (Universitas Islam Negeri Sunan Ampel Surabaya, 2024)
Happiness, as the ultimate goal of every individual, continues to be a never-ending topic of discussion. In this study, focus is placed on two great Muslim philosophers, Al-Ghazali and Al-Farabi, who have different philosophical backgrounds. Al-Farabi, an Aristotelian, and Al-Ghazali, a sharp critic of this school, encourage us to explore the nature and approach to happiness from their perspectives. Taking into account the differences in their philosophical backgrounds, this study aims to detail the ideas related to happiness promoted by Al-Ghazali and Al-Farabi. Through descriptive analysis and literature study, this research reveals the essence of happiness in their views and explores practical ways to achieve it. The results of this study show that both Al-Ghazali and Al-Farabi agree that true happiness can only be achieved through deep knowledge of God. However, both have different characteristics in the path to happiness